Computational modeling for large wood dynamics with root wad and anisotropic bed friction in shallow flows. (November 2018) - Kang, Taeun; Kimura, Ichiro
Highlights: We developed a computational model for motion of large wood (LW) in shallow flows. Lagrange type LW motion model was coupled with Euler type shallow flow model. The laboratory tests were performed with different flow discharge and channel slope. Rolling, sliding and depositing motions of LW were simulated accurately. The root wad of wood piece reduced the velocity of wood motion in shallow flows. Abstract: This study developed a computational model for large wood deposition patterns in shallow flows considering the effect of a root wad based on laboratory experiments. We used the Nays2DH depth-averaged two-dimensional model of iRIC to simulate shallow flows. A newly developed large wood simulation model was combined with the shallow flow model. The laboratory tests were performed by changing several hydraulic parameters. In shallow water with a depth similar to the diameter of large wood, the root wad decreased the draft for wood motion (the depth at which large wood contacts the river bed) by lifting the head of large wood. The experimental results showed that the large wood tends to move toward the side walls and deposit on the bed after passing an obstacle. Computational results reasonably showed that the proposed coupling model reproduced the fundamental and physical aspects of the phenomena.